2011
DOI: 10.4331/wjbc.v2.i9.202
|View full text |Cite
|
Sign up to set email alerts
|

p53 in stem cells

Abstract: p53 is well known as a "guardian of the genome" for differentiated cells, in which it induces cell cycle arrest and cell death after DNA damage and thus contributes to the maintenance of genomic stability. In addition to this tumor suppressor function for differentiated cells, p53 also plays an important role in stem cells. In this cell type, p53 not only ensures genomic integrity after genotoxic insults but also controls their proliferation and differentiation. Additionally, p53 provides an effective barrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 130 publications
3
49
1
Order By: Relevance
“…One possible explanation for this switch is that p53 deficiency Color images available online at www .liebertpub.com/scd may have altered the cell context so that neuronal differentiation process differently responds to Id1, which warrants further investigation. Together with the findings that p53 also represses Id2, which also participates in NSC selfrenewal [25,59], our results suggest an important link between p53 and Id proteins.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…One possible explanation for this switch is that p53 deficiency Color images available online at www .liebertpub.com/scd may have altered the cell context so that neuronal differentiation process differently responds to Id1, which warrants further investigation. Together with the findings that p53 also represses Id2, which also participates in NSC selfrenewal [25,59], our results suggest an important link between p53 and Id proteins.…”
supporting
confidence: 86%
“…Recently, p53 has been shown to negatively control the proliferation of NSCs and p53 deficiency facilitates glioblastoma development via Myc and p21 [23]. However, it is still uncertain how p53 regulates neural differentiation as conflicting results have been reported (reviewed in [18,24,25]). While several studies show that p53 inhibits neuronal lineage, there are studies showing that p53 plays no effect on neuronal differentiation [23,[26][27][28][29][30].…”
mentioning
confidence: 99%
“…One particularly relevant TPT1/TCTP interactor is the P53 tumor-suppressor protein. Although it was previously reported [18] that overexpression of P53 resulted in decreased levels of TPT1/TCTP, it was only recently demonstrated that TPT1/TCTP is a key regulator of P53 stability and activity [23] with possible consequences on the homeostasis of the SC compartment [23,[70][71][72][73][74][75] (Box 1). Mechanistically, TPT1/TCTP downregulates P53 by promoting its ubiquitination by the E3-ligase Mdm2 and subsequent proteasomal degradation [23] (Figure 4).…”
Section: Tpt1/tctp In Reprogramming: From Scs To Tumor Reversionmentioning
confidence: 99%
“…In this context, the tumor suppressor P53 is emerging as a critical regulator of SC homeostasis in different types of tissues, including the mammary gland [71]. Increased wild type (WT) p53 activity in the murine mammary gland leads to aberrant morphogenesis and reduction of the self-renewal potential of mammary SCs, demonstrated by serial transplantation experiments [72].…”
Section: Box 1 Breast Cancer Scsmentioning
confidence: 99%
“…12 Recently, mounting evidence suggests that p53 also controls the proliferation, self-renewal, and differentiation of embryonic and adult stem cells to maintain tissue or organ homeostasis. 13 This raises the question of whether the molecular pathways that p53 employs under genotoxic stress might also function under normal physiological conditions. For example, upon DNA damage, p53 negatively regulates mTORC1 activity to limit metabolic support, prevent cell division, and cause cellular quiescence, thereby exerting its function as a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%